DI-001 Analysis of the use, effectiveness and safety of treatment with Trastuzumab-Emtansine in metastatic breast cancer. (24th March 2015) - Diaz, M; Manuel, C; Ana, V; Esther, D; Sergio, P; Eva Maria, G; Nuria, M; Gregorio, R; Jose, M
Abstract : Background: Trastuzumab-emtansine (TDM1) is designed to inhibit the HER2 pathway and directly release DM1 chemotherapy inside HER2-positive cells. Purpose: To analyse the use, progression-free survival (PFS) and adverse drug reactions (ADRs) in patients with metastatic breast cancer treated with TDM1. Material and methods: Retrospective observational study including all women treated with trastuzumab-emtansine from March to October 2014. To obtain data, the electronic medical record (XXI Mambrino) was reviewed and analysed using SPSS. The variables were age, line of treatment, ADRs and PFS. ADRs were classified according to Common Toxicity Criteria v4.0. The effectiveness variable was PFS. Results: Five women (median age 51 years old (39–64)) were included at the beginning of the treatment. In 2 of them trastuzumab-emtansine was used in 1st line treatment of metastases; while in the rest it was used in 3rd, 5th and 6th line. The most frequent ADRs according to their severity were thrombocytopenia G2 and enzymatic hepatic alterations G3. The rest of the ADRs were mild and as described in the literature. Regarding PFS, 2 of the 5 patients progressed, obtaining a median PFS of 6 months. The other three patients have a median follow-up of 5 months to the time of writing. Conclusion: The use of TDM-1 is off-label in 2 of the 5 cases. One is being used first line with a progression time exceeding 6 months (10 months) and the other due to the inability to use the combination pertuzumab-trastuzumab-docetaxel due to prior taxane-induced neuropathy. The median PFS (6 months) was lower than that obtained in clinical studies (EMILIA 9.6 months, compared to lapatinib-capecitabine and TH3ERESA 6.2 months, compared to a medical treatment choice in patients who have previously been treated with both trastuzumab and lapatinib). Currently 3/5 patients continue with the treatment, thus, the median PFS will increase. TDM-1 by its toxicity profile has been a safe drug in our cases. References and/or acknowledgements: No conflict of interest.